Neurotensin inhibits AMPK activity and concurrently enhances FABP1 expression in small intestinal epithelial cells associated with obesity and aging - Jing Li; Jun Song; Baoxiang Yan; Haoming Wu; Moumita Banerjee; Leif Magnuson; Yajuan Liu; Shulin Zhang; Jinpeng Liu; Chi Wang; Tianyan Gao; Jianhang Jia; et al. (Experimental and Molecular Medicine)
Abstract We previously demonstrated that neurotensin, a 13-amino-acid gut hormone peptide, enhances small intestinal epithelial cell fatty acid uptake through inhibition of AMPK. Here, utilizing Drosophila and mouse models in vivo, as well as mouse and human small intestinal epithelial organoids or monolayers ex vivo, we determine the targets of neurotensin and AMPK associated with obesity and aging. High-fat diet and aging decreased AMPK and insulin signaling, which was prevented by neurotensin deficiency. High-fat diet feeding increased FABP1 protein expression in wild-type mice; this effect was attenuated in neurotensin-deficient mice. AICAR and metformin increased AMPK phosphorylation in young but not in aged small intestinal epithelial cells. By contrast, AICAR and metformin inhibited FABP1 mRNA and protein expression. Moreover, cytosolic colocalization of AMPKα1 and FABP1 was noted in IEC-6 cells. AMPK phosphorylation and FABP1 expression was decreased in aged wild-type small intestinal epithelial cells; however, this effect was reversed in neurotensin-deficient cells. Results from human duodenal organoids confirm the effects of neurotensin, palmitic acid and metformin on AMPK phosphorylation and FABP1. Finally, overexpressing neurotensin in enteroendocrine cells reduced the lifespan of Drosophila; neurotensin deficiency extended the lifespan of mice fed a high-fat diet. Our findings indicate that neurotensin inhibits AMPK and increases FABP1 in small intestinal epithelial cells under conditions of obesity. Neurotensin deficiency preserves AMPK and FABP1 levels, thus attenuating some of the negative effects of obesity and aging.